2017
DOI: 10.1111/jav.01287
|View full text |Cite
|
Sign up to set email alerts
|

Variation in laying date in relation to spring temperature in three species of tits (Paridae) and pied flycatchers Ficedula hypoleuca in southernmost Sweden

Abstract: This study documents the advancement of laying dates in three species of tits (Paridae) in southernmost Sweden during recent decades, and the absence of a similar response in the pied flycatcher Ficedula hypoleuca. It is based on several different nestbox studies; the oldest one starting in 1969. During 1969 to 2012, mean spring temperatures in the study area increased by between 0.06 and 0.08°C per year, depending on the period considered. Great tits Parus major, blue tits Cyanistes caeruleus and marsh tits P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
26
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(29 citation statements)
references
References 57 publications
3
26
0
Order By: Relevance
“…Our results clearly demonstrate that resident tit populations are generally more flexible in adjusting to variation in temperatures than migratory flycatcher populations from the same breeding areas. The large geographical scale at which our analysis was performed allows us to draw more general conclusions about this pattern than previous studies, one of which corroborated our findings (Phillimore et al., ), while another did not (Källander et al., ). We further found that, in contrast to a previous study (Both et al., ), flycatchers in areas that warmed more did not also advance their laying dates more over time, but we found that pattern to hold for tits.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Our results clearly demonstrate that resident tit populations are generally more flexible in adjusting to variation in temperatures than migratory flycatcher populations from the same breeding areas. The large geographical scale at which our analysis was performed allows us to draw more general conclusions about this pattern than previous studies, one of which corroborated our findings (Phillimore et al., ), while another did not (Källander et al., ). We further found that, in contrast to a previous study (Both et al., ), flycatchers in areas that warmed more did not also advance their laying dates more over time, but we found that pattern to hold for tits.…”
Section: Discussionsupporting
confidence: 89%
“…Two recent long‐term studies gave contrasting evidence to the hypothesis that migrants adjust their laying dates to a lesser extent to temperature than sympatric residents: in the UK, the migratory pied flycatcher, Ficedula hypoleuca , was less sensitive in its laying date response to spring temperature (−2.3 days/°C) than resident tits (−4.8 days/°C) (Phillimore, Leech, Pearce‐Higgins, & Hadfield, ). In contrast, in Sweden, the difference in response between flycatchers and tits was mostly absent (pied flycatchers: mean: −1.62 days/°C ( N = 3 time series; SE : 0.19); blue tits, Cyanistes caeruleus and great tits, Parus major : mean: −1.90 days/°C ( N = 6 time series; SE =0.14); time series from 1970/80s to 2010s, Källander et al., ). The causes of these contrasting patterns are unclear, but could in part be due to differential time series durations or differential methodologies.…”
Section: Introductionmentioning
confidence: 98%
“…Two well-known examples are earlier egg laying to track warming springs and increased mortality under extreme weather events. Warmer spring temperatures in temperate and high latitudes have induced phenological shifts to synchronize the start of reproduction with earlier leafing and flowering of plants and the consequently advanced peak of caterpillar abundance (Crick et al, 1997;Visser et al, 1998;Dunn and Winkler, 1999;Sanz, 2002;Charmantier et al, 2008;Källander et al, 2017). Extreme weather events, such as heat waves, occur with increasing frequency around the globe and are predicted to continue to do so (Coumou and Robinson, 2013;Mutiibwa et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In general, warmer conditions at the start of a breeding season favor earlier egg‐laying initiation dates (Dunn , Visser and Both , Visser et al , Ockendon et al , Phillimore et al ). The long‐term trend toward earlier egg laying by species exposed to increasing spring temperatures due to climate change has also been widely documented (Matthysen et al , Charmantier and Gienapp , Dunn and Møller , Phillimore et al , Källander et al , Samplonius et al ).…”
Section: Discussionmentioning
confidence: 90%